Seat of The Divine Preserver: Prabudewa Iconographies of The Hamengku Buwana Dynasty - Supriyadi, Matheus Raoul (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
For more than two-and-a-half centuries, the Sultanate of Yogyakarta has been under the rule of one dynasty of sultans called the Hamengku Buwana. One of the keys to such a prolonged rulership by one dynasty is the use of narratives as well as symbolisms that support said narratives. In the case of the sultanate, the narratives relate the rulers to the concept of the sultan as a god-king, or in the Javanese term, prabudewa. In this article, I explore how the dynasty found means of identification with the Hindu deity, Lord Vishnu, to strengthen the claim that the sultan is indeed a divine sovereign. Using the symbolic framework, I argue that the Hamengku Buwana have used artistic allusions to Lord Vishnu which are incorporated in the court's iconographies to reach that goal. At the end of the day, I found that the dynasty has, in fact, been using artistic iconographies within the royal court as a means to strengthen their identification as Lord Vishnu, the divine preserver of the universe according to the Hindu pantheon. The iconographies are spread throughout the royal court and can be found in various forms as well which one can still see to this day, such as the royal coach, the sultan's throne room, and in Yogyakartan batik motifs.